Keterampilan motorik dan prestasi akademik - Soleh Solahuddin; Wahyu Indra Bayu; Topo Yono; Suci Nanda Sari; Reza Resah Pratama (Ilmu Olahraga, 2023)
Motor development is a process in which children begin to learn to move their limbs skillfully. The opportunity to learn motor skills is very large in the motor development period of early childhood. Good motor skills can certainly have positive implications for various fields in a child's life, one of which is academic achievement. This study used the method of literature review, which was conducted to identify the correlation between motor skills and academic achievement. The 10 scientific journals published the longest in 2013 and the latest in 2021 accessed through NCBI and Research Gate were used as data sources in this study. Search data sources using a combination of keywords motor skills and academic achievement. In general, there is a correlation between motor skills and academic achievement, but there is a different correlation between specific motor skills and certain academic achievements. Future research can look at the correlation of motor skills and academic achievement more specifically or conduct research with students with special needs participants.